Type 2 cytokine genes as allergic asthma risk factors after viral bronchiolitis in early childhood - Dong, Zihan; Myklebust, Åsne; Johnsen, Ingvild Bjellmo; Jartti, Tuomas; Døllner, Henrik; Risnes, Kari; DeWan, Andrew T. (Frontiers in Immunology, 2023)
Background: Genome-wide association studies of asthma have identified associations with variants in type-2 related genes. Also, specific interactions between genetic variants and viral bronchiolitis in the development of asthma has been suggested. Objective: To conduct a gene-based analysis of genetic variants in type 2 cytokine related genes as risk factors for allergic asthma at school age, and further, to study their interaction with specific viral infections in early childhood. Methods: A prospectively investigated cohort of children with previous bronchiolitis and controls came for follow-up at school age. The research visit, blinded to viral exposure, included detailed lung function tests, laboratory investigation, and questionnaires. Allergic asthma was defined as typical symptoms plus objective variable airway obstruction, in addition to laboratory verified atopy (elevated eosinophil count or sensitization to an allergen). Targeted and complete sequencing was performed for nine type 2 cytokine candidate genes: IL3, 5, 13, 25, 33 and 37, IL17RB, CRLF2 and TSLP. Results: At follow-up, there were 109 children with genetic data, 91 with a history of bronchiolitis (46% respiratory syncytial virus, 24% human rhinovirus, 15% human metapneumovirus and 14% mixed viral etiology) and 18 without. The median age was 9.4 years (range 6-13) and 41 (38%) had laboratory verified atopy. Twenty-one children (19%) met the definition of allergic asthma. After adjusting for age, sex and five viral categories, IL33 achieved nominal significance (p = 0.017) for a positive association with allergic asthma development. In the gene-virus interaction analysis, the variant set in IL17RB demonstrated a nominally significant positive interaction with human metapneumovirus infection (p=0.05). Conclusion: The results highlight the multifactorial nature of allergic asthma risk, with both viral infection and inherited genetic variants contributing to increasing risk. Results for IL33 and IL17RB were nominally significant and are potential candidate targets for designing therapeutics and early screening, but these results must be replicated in an independent study.